Fate of sulfur mustard on soil: Evaporation, degradation, and vapor emission. (January 2017) - Jung, Hyunsook; Kah, Dongha; Chan Lim, Kyoung; Lee, Jin Young
Abstract: After application of sulfur mustard to the soil surface, its possible fate via evaporation, degradation following absorption, and vapor emission after decontamination was studied. We used a laboratory-sized wind tunnel, thermal desorber, gas chromatograph-mass spectrometry (GC-MS), and 13 C nuclear magnetic resonance ( 13 C NMR) for systematic analysis. When a drop of neat HD was deposited on the soil surface, it evaporated slowly while being absorbed immediately into the matrix. The initial evaporation or drying rates of the HD drop were found to be power-dependent on temperature and initial drop volume. Moreover, drops of neat HD, ranging in size from 1 to 6 μL, applied to soil, evaporated at different rates, with the smaller drops evaporating relatively quicker. HD absorbed into soil remained for a month, degrading eventually to nontoxic thiodiglycol via hydrolysis through the formation of sulfonium ions. Finally, a vapor emission test was performed for HD contaminant after a decontamination process, the results of which suggest potential risk from the release of trace chemical quantities of HD into the environment. Graphical abstract: Highlights: The initial evaporation rates of HD from soil are heavily dependent on temperature, wind speed, and drop size. Persistent HD degrades to nontoxic thiodiglycol via hydrolysis through the formation of sulfonium ions. Vapor emission rates of HD remaining after decontamination were determined from soil.